La poésie antique du Sangam est-elle vraiment une poésie du paysage ? Littérature tamoule classique et vision contemporaine du paysage - Frédéric Landy; Evelyne Gauché; Gopinath Sricandane (VertigO)
The Tamil “Sangam” poetry, which is two millennia old, is often described as "landscape poetry". It could be compared to the Chinese shanshui poetry, which is slightly later (4th century AD). To what extent did the Indian poets of that time pay real attention to the landscape? Could it be that this literature is, according to the expression of A. Berque (2016), a real "thought of landscape"? Indeed, emotions and a whole "inner landscape" are reflected in it. In particular, a word often used by later medieval commentators to classify the poems is commonly translated as "landscape". Yet this term, tinai, is very rare in the works themselves. The article describes the successive avatars of this poetry and the notion of tinai in Tamil memory and contemporary society. Nowadays, a regionalist reading, often very political, has contributed to fossilize the poems under this label of landscape literature.